2003
DOI: 10.1038/sj.bjp.0705505
|View full text |Cite
|
Sign up to set email alerts
|

The rabbit motilin receptor: molecular characterisation and pharmacology

Abstract: 1 Following identification of the human motilin receptor, we isolated the rabbit orthologue by PCR amplification and found this to be 85% identical to the open reading frame of the human receptor. The protein encoded was 84% identical to the human polypeptide. ]-motilin faded rapidly during its continual presence. Rat or human ghrelin 0.01 -10 mM were without activity. 4 Erythromycin 30 -3000 nM and 10 mM, respectively, increased neuronal activity and muscle tension in rabbit stomach. Unlike [Nle 13 ]-motili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
72
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 22 publications
6
72
1
Order By: Relevance
“…Preliminary studies have shown that motilin can stimulate the ghrelin receptor, albeit at a low level. In contrast, ghrelin does not activate motilin receptor (53).…”
Section: A the Ghrelin Receptor Familymentioning
confidence: 93%
“…Preliminary studies have shown that motilin can stimulate the ghrelin receptor, albeit at a low level. In contrast, ghrelin does not activate motilin receptor (53).…”
Section: A the Ghrelin Receptor Familymentioning
confidence: 93%
“…This initial report revealed these novel GPCRs to be related to the ghrelin and neurotensin receptors. GPR38 has since been identified as the cognate receptor for motilin, a 22 amino acid peptide that regulates gastrointestinal (GI) motility [2,3]. In 2005, Zhang et al implicated GPR39 to be the receptor for obestatin [4], a peptide encoded by the ghrelin gene.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrated peptide solutions (1 mg/ml) were prepared in PBS and stored as 20-l aliquots in Eppendorf vials at Ϫ80°C until use. Motilin concentrations used had previously been shown to elicit a response in vitro (10,28).…”
mentioning
confidence: 99%